2019
DOI: 10.1302/0301-620x.101b12.bjj-2019-0462.r2
|View full text |Cite
|
Sign up to set email alerts
|

The formation of perianchor fluid associated with various suture anchors used in rotator cuff repair

Abstract: Aims The aim of this study was to compare the osseous reactions elicited by all-suture, polyetheretherketone (PEEK), and two different biodegradable anchors used during rotator cuff repair. Patients and Methods Transosseous-equivalent rotator cuff repair was performed in 73 patients. The patients were divided into two groups, in both of which two different medial-row anchors were used. In group 1, anchor A comprised 30% β-tricalcium phosphate (TCP) + 70% fast-absorbing poly lactic-co-glycolic acid copolymer (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Furthermore, we observed a reduced incidence of edema in patients treated with all-suture anchors. However, we did not note any relationship between the dislocations (measured by MR) and the functional results obtained and the patients’ quality of life, thus confirming the thesis expressed by S. H. Kim et al [ 23 ], regarding the non-correlation between the presence of perianchor edema and the functional result of the repair. We also found no significant differences from the results obtained for patients treated with the healix system.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, we observed a reduced incidence of edema in patients treated with all-suture anchors. However, we did not note any relationship between the dislocations (measured by MR) and the functional results obtained and the patients’ quality of life, thus confirming the thesis expressed by S. H. Kim et al [ 23 ], regarding the non-correlation between the presence of perianchor edema and the functional result of the repair. We also found no significant differences from the results obtained for patients treated with the healix system.…”
Section: Discussionsupporting
confidence: 89%
“…However, previous reports have shown that different anchor types do not affect cuff healing. 25,26 Seventh, 24 cases (12 patients) of the 316 cases involved bilateral arthroscopic rotator cuff repair surgery. Of those patients, 5 patients did not receive an antiadhesive agent in either shoulder, 1 patient received a thermosensitive antiadhesive agent in both shoulders, and 6 patients received a thermosensitive antiadhesive agent in only 1 shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…PEEK + biodegradable 2) using a double-row rotator cuff repair. 14 Their study showed a statistically significant higher rate of PCF around PEEK anchors (41.7%, 15/36) than ASAs (10.8%, 4/37), P < .05. When the ASA was compared to the biodegradable anchor used in the same patient, there was no statistical difference as seen in our study.…”
Section: Discussionmentioning
confidence: 87%